The impact of brand equity on vertical integration in franchise systems - Mohammad Kayed; Manish Kacker; Ruhai Wu; Farhad Sadeh (Journal of Retailing, 2025)
Brand equity and vertical integration are focal, strategic elements of a franchise system that can profoundly influence franchise performance. Despite the recognized importance of these two strategic levers and the longstanding research interest in the topic, our understanding of the interplay between brand equity and vertical integration (company ownership of outlets) in a franchise system remains incomplete. In this study, we revisit the five-decade-old question of how brand equity affects vertical integration in a franchise system and present some novel, nuanced insights into the topic. Evidence from a Bayesian Panel Vector Autoregressive model on a large panel data set shows that brand equity has a powerful, lagging inverse effect on vertical integration, such that higher brand equity leads to less downstream vertical integration in a franchise system. Reverse causality analyses identify a less pronounced but present reciprocal effect. Boundary conditions analyses reveal that the negative effect of brand equity on vertical integration is weaker in franchise systems with international presence and in retail-focused (vs. service-focused) franchises, and stronger in franchise systems with more financial resources. These findings (a) challenge traditional views (e.g., transaction cost theory, resource-based view, ownership redirection hypothesis) on the topic by demonstrating a negative effect for brand equity on vertical integration in franchise systems and showing that greater financial resources amplify this effect, and (b) shed new light on the intricate dynamics (temporal causation, reverse causation) and contingencies of this debated effect. Managerially, this research draws attention to the underrecognized strategic benefit of brand equity in mitigating channel governance issues and advise against unnecessary vertical integration, especially when brand equity is robust.
Keywords: 650; Vertical integration; Brand equity; Franchising; Retailing